Lansia Bahagia di Masa Tua: Peningkatan Kualitas Hidup melalui Aktivitas Harian Menyenangkan - Wahyu Dini Candra Susila; Nurwahidah Nurwahidah; Hanny Rasni; Erti Ikhtiarini Dewi (Kifah: Jurnal Pengabdian Masyarakat, 2026)
Functional decline and limited access to health services in rural areas are contributing factors to the low quality of life of the elderly. This community service program aims to improve the quality of life of the elderly through the implementation of community-based Activity Daily Living (ADL) fulfillment activities. The method used is the Community Based Research (CBR) approach which includes four stages: laying the foundation, planning, information gathering and analysis, and acting on finding. The activity was implemented through participatory education with interactive lecture techniques and practical simulations involving 100 elderly in Karangwerdha Ledokombo, Jember. The program evaluation was conducted using a knowledge questionnaire on quality of life through a pre-test and post-test mechanism. The results of the activity showed an increase in the quality of life of participants as indicated by an increase in the average score from 59.68 in the pre-test to 74.23 in the post-test. This increase was supported by the high participation of elderly in activities and the presence of social support from the surrounding environment. This activity concluded that community-based interventions through the fulfillment of ADL activities are effective in improving the quality of life of the elderly. Strengthening family and social support on an ongoing basis is needed to support the realization of healthy, independent, and productive elderly.